2020
DOI: 10.3390/biomedicines8080252
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nargenicin A1 Analog Inhibits Angiogenesis by Downregulating the Endothelial VEGF/VEGFR2 Signaling and Tumoral HIF-1α/VEGF Pathway

Abstract: Targeting angiogenesis is an attractive strategy for the treatment of angiogenesis-related diseases, including cancer. We previously identified 23-demethyl 8,13-deoxynargenicin (compound 9) as a novel nargenicin A1 analog with potential anticancer activity. In this study, we investigated the antiangiogenic activity and mode of action of compound 9. This compound was found to effectively inhibit in vitro angiogenic characteristics, including the proliferation, invasion, capillary tube formation, and adhesion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Similar to compound 9 treatment, CypA silencing reduced the expression of CD147 and the phosphorylation of JNK and ERK1/2. Furthermore, the suppressive effects of CypA silencing on the proliferation, migration, invasion, and angiogenesis induction of AGS cells were associated with G2/M cell cycle arrest, caspase-mediated apoptosis, inhibition of MMP-9 and MMP-2 expression, inactivation of PI3K/AKT/mTOR pathway, and inhibition of HIF-1α and VEGF expression, consistent with the effects of compound 9 reported in our previous studies [ 14 , 15 ]. Taken together, our findings imply that CypA regulates CD147 expression in GC, and thus, it affects CD147-mediated downstream signaling and subsequent cellular response.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to compound 9 treatment, CypA silencing reduced the expression of CD147 and the phosphorylation of JNK and ERK1/2. Furthermore, the suppressive effects of CypA silencing on the proliferation, migration, invasion, and angiogenesis induction of AGS cells were associated with G2/M cell cycle arrest, caspase-mediated apoptosis, inhibition of MMP-9 and MMP-2 expression, inactivation of PI3K/AKT/mTOR pathway, and inhibition of HIF-1α and VEGF expression, consistent with the effects of compound 9 reported in our previous studies [ 14 , 15 ]. Taken together, our findings imply that CypA regulates CD147 expression in GC, and thus, it affects CD147-mediated downstream signaling and subsequent cellular response.…”
Section: Discussionsupporting
confidence: 90%
“…We previously found that compound 9 decreased in vitro AGS cell-induced angiogenesis of HUVECs by blocking the expression of HIF-1α and VEGF in AGS cells [ 15 ]. To assess whether CypA knockdown affects the angiogenic properties of HUVECs induced by AGS cells, conditioned medium (CM) was obtained from AGS cells and used as an angiogenic stimulus for the proliferation and invasion of HUVECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-1α is stably expressed under hypoxia; it can regulate EPO and VEGF expression and promote RNV[ 44 , 45 ]. Inhibiting the VEGF/VEGFR2 and HIF-1α/VEGF signaling pathways can prevent angiogenesis[ 46 ]. TGF-β2 is a pro-inflammatory cytokine precursor related to the pathogenesis of DR. IGF1 has been identified as the direct target of miR-142-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 9 is a new analog of nargenicin A1, an antibacterial macrolide with effective activity against various Gram-positive bacteria [ 83 ]. It possesses potential antitumor and antiangiogenic activity, unlike nargenicin A1 [ 83 , 99 ]. Proteomics analysis and further functional studies demonstrated that compound 9 binds to CypA and downregulates the CD147-mediated MAPK signaling pathway, including JNK and ERK1/2, by inhibiting CypA and CD147 expression in gastric cancer cells [ 13 ].…”
Section: Therapeutic Potential Of Targeting Cypa/cd147 In Cancermentioning
confidence: 99%